An introduction to the philosophy of practical reason - Sylvan, K; Chang, R (Routledge, 2020)
This introduction presents an overview of the key concepts discussed in the subsequent chapters of the book. This book provides a survey of research in the philosophy of practical reason, with some attention to the history of philosophy, but with an overall focus on the contemporary analytic tradition. The philosophy of practical reason has its roots in decades of scattered work originally written within more established areas of philosophy, especially action theory, ethics, metaethics, philosophy of mind, moral psychology, and the theory of rationality. In contrast to the concept of a motivating practical reason, there is the concept of a normative practical reason. One of the most important critics of that argument and one of the most important defenders of subjectivism is David Sobel. Sobel outlines a strategy of argument for subjectivism that has three stages: offense, non-moral defense, and moral defense.